Boko Haram: security considerations and the rise of an insurgency - Ekhomu, Ona (CRC Press, 2020)
"Boko Haram analyzes the activities and atrocities of Nigeria's Jihadi terrorist group, Boko Haram in the context of global religious fundamentalism and extremism. The book traces the early beginnings of the religious sect, the conversion of its leader to radical Islam in 2002, and the group's campaign of violence beginning in 2009 and continuing to the present. The group's attacks against a variety of targets are examined in detail as are their general tactics and strategies. The Nigerian government response is also examined in order to provide critical lessons to counter-terrorism planners, officials and scholars. The initial military response was hampered by capability and legislative constraints including lack of arms and ammunitions, lack of modern counter-terrorism equipment, training gap, leadership issues, intelligence gap, politicization of the conflict, and limited support for the Nigerian Military by the international community. The book looks at the work that has been done thus far, and what work needs to continue, to make gains to combat, marginalize, and ultimately defeat Boko Haram and resolve the conflict facing Nigeria."--Provided by publisher